2012
DOI: 10.1902/jop.2011.110281
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Photodynamic Therapy, Diode Laser, and Deep Scaling on Cytokine and Acute‐Phase Protein Levels in Gingival Crevicular Fluid of Residual Periodontal Pockets

Abstract: Levels of several cytokines and acute-phase proteins significantly changed after treatment regardless of treatment modality. There was no evidence for a specific DSL- or PDT-enhanced expression of inflammatory mediators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
124
1
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(144 citation statements)
references
References 44 publications
(48 reference statements)
8
124
1
9
Order By: Relevance
“…No significant differences were observed among the three treatment modalities at any time point for haptoglobin [26].…”
Section: Haptoglobinmentioning
confidence: 82%
“…No significant differences were observed among the three treatment modalities at any time point for haptoglobin [26].…”
Section: Haptoglobinmentioning
confidence: 82%
“…[49][50][51] Three out of the 8 studies have also evaluated the changes in terms of inflammatory markers. 47,50,52 Two studies have revealed statistically significantly higher reductions in the investigated inflammatory markers following the use of PDT, 47,50 while one study detected no differences 52 (Table 3). …”
Section: Use Of Pdt As Adjunct To Nonsurgical Periodontal Therapy In mentioning
confidence: 97%
“…Dessa forma, as três concentrações do azul de toluidina e azul de metileno utilizadas foram 0,05 mg/ml (BERAKDAR et al, 2012;BALATA et al, 2013;PINHEIRO et al, 2010) ,0,1 mg/ml (AL-ZAHRANI et al, 2009;GE et al, 2011;NORO FILHO et al, 2012;THEODORO et al, 2012;BASSIR et al, 2013;FRANCO et al, 2014;MONGARDINI;DI TANNA;PILLONI, 2014) e 10 mg/ml (DE OLIVEIRA et al, 2007;CHRISTOULIDES et al, 2008;CHONDROS et al, 2009;DE OLIVEIRA et al, 2009;LULIC et al, 2009;POLANSKY et al, 2009;SIGUSCH et al, 2010;CAPPUYNS et al, 2012;GIANNOPOULOU et al, 2012;NOVAES et al, 2012;ANDRADE et al, 2013;CAMPOS et al, 2013;LUCHESI et al, 2013;SOUZA et al, 2013;ARWEILER et al, 2014;BETSY et al, 2014;KOLBE et al, 2014;MACEDO et al, 2014;MOREIRA et al, 2014;PETELIN et al, 2014;QUEIROZ et al, 2014;ALWAELI;KHATEEB;AL-SADI, 2015;QUEIROZ et al, 2015). Apesar dos resultados do teste de concentração dos corantes, onde a concentração de 10mg/ml foi a única efetiva para o metileno e a de 5 e 10mg/ml foram as bactericidas para o toluidina, optamos por testar novamente as três concentrações mais comum na literatura acima citada.…”
Section: Discussionunclassified
“…Outros estudos também aplicam essa potência (BRAUN et al, 2008;RÜHLING et al, 2010;GIANNELLI et al, 2012;GIANNOPOULOU et al, 2012;BALATA et al, 2013;DILSIZ;CANAKCI;AYDIN, 2013;ALWAELI;KHATEEB;AL-SADI, 2015). Porém ,outro valor de potência frequentemente encontrado é entre 60 mW e 75 mW (DE OLIVEIRA et al, 2007;CHRISTOULIDES et al, 2008;CHONDROS et al, 2009;DE OLIVEIRA et al, 2009;LULIC et al, 2009;POLANSKY et al, 2009;SIGUSCH et al, 2010;ANDRADE et al, 2013;CAMPOS et al, 2013;LUCHESI et al, 2013;SOUZA et al, 2013;BETSY et al, 2014;CHITSAZI et al, 2014;FRANCO et al, 2014;KOLBE et al, 2014;MACEDO et al, 2014;PETELIN et al, 2014;QUEIROZ et al, 2014;QUEIROZ et al, 2015).…”
Section: Discussionunclassified
See 1 more Smart Citation